Communication Between Mothers and Children with Mental Disorders - Magfirah Mukhtar, St. Hajar; Alimuddin Unde, Andi; Fatimah Maria, Jeanny (KnE Social Sciences, 2023)
Parental communication affects children’s mental health. This research aimed to understand communication between working parents and children with mental disorders. This research focused on two issues: the effectiveness of parents’ communication and parents’ communication patterns. This was a qualitative study. Researchers interviewed five mothers. The criteria for selecting the participants were based on the number of working hours being over 42 hours per week, children aged 5-18 years, children showing symptoms of mental illness according to the SDQ (Strengths and Difficulties Questionnaire), and having children who lived in cities. Macassar. All five informants were women who worked as government employees, traders, bank employees, and private employees. The interview was semi-structured. Thematic analysis was used to analyze participants’ answers. The results showed that parents experienced the two cases of communication that were initially identified in this study, implementing effective communication and implementing communication patterns in their families. This study recommends further research to be conducted in other cities and with a more diverse sample as a comparison. Keywords: Communication Effectiveness; Communication Patterns; Mental Health